Progress in the knowledge of irregular solid electrode surfaces - Arvia, Alejandro Jorge (1994)
Modern approaches to solid surface disorder provide a more rigourous way of defining roughness at solid surfaces, a crucial concept in electrocatalysis. The study of this type of surface comprises growth kinetics, geometric description, relaxation kinetics and influence of surface irregularities on different reactions. Continuous rough columnar structured metal surfaces constitute a good model system for the investigation of a number of processes which are of special interest in heterogeneous catalysis, including electrocatalysis. The topography of these metal surfaces can be determined by scanning tunneling microscopy (STM) at different scales and can be described by means of the dynamic scaling theory applied to STM imaging. Roughness relaxation kinetics followed by electrochemical techniques can be interpreted through a coalescence-type mechanism. Typical examples of adsorption and diffusion controlled electrochemical reactions on this type of electrodes are presented.